2006
DOI: 10.1007/11758525_107
|View full text |Cite
|
Sign up to set email alerts
|

Simple Reconstruction of Binary Near-Perfect Phylogenetic Trees

Abstract: Abstract.We consider the problem of reconstructing near-perfect phylogenetic trees using binary character states (referred to as BNPP). A perfect phylogeny assumes that every character mutates at most once in the evolutionary tree, yielding an algorithm for binary character states that is computationally efficient but not robust to imperfections in real data. A near-perfect phylogeny relaxes the perfect phylogeny assumption by allowing at most a constant number q of additional mutations. In this paper, we deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Even in this restricted setting, the Steiner tree problem has been shown to be NP-complete [21]. However, the phylogeny reconstruction problem when the optimal phylogeny is q-near-perfect can be solved in time polynomial in n and m when q = O(log(poly(n, m))) [17]. If q is very large, though, such algorithms do not perform well.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in this restricted setting, the Steiner tree problem has been shown to be NP-complete [21]. However, the phylogeny reconstruction problem when the optimal phylogeny is q-near-perfect can be solved in time polynomial in n and m when q = O(log(poly(n, m))) [17]. If q is very large, though, such algorithms do not perform well.…”
Section: Definitionmentioning
confidence: 99%
“…The standard in practice is the use of sophisticated heuristics that will always produce a tree but cannot guarantee optimality (e.g., [11], [12], [13]). Some theoretical advances have recently been made in the efficient solution of near-perfect phylogenies, those that deviate only by a fixed amount from the assumption of perfection [14], [15], [16], [17]. These methods can provide provably efficient solutions in many instances, but still struggle with some moderate-size data sets in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, the major determinant of run time appears to be a dataset's imperfection, i.e., the difference between the optimal length and the number of variant sites. It has recently been shown that the phylogeny problem under various assumptions is fixed parameter tractable in imperfection [6,13,31,32] possibly suggesting why it is a critical factor in run time determination. The pars program of phylip, despite providing no guarantees of optimality, does indeed find optimal phylogenies in all of the above instances.…”
Section: Resultsmentioning
confidence: 99%
“…Even in this restricted setting, the Steiner tree problem has been shown to be NP-complete [14]. However, the phylogeny reconstruction problem when the optimal phylogeny is q-near-perfect can be solved in time polynomial in n and m when q = O(log(poly(n, m))) [32]. If q is very large, though, such algorithms do not perform well.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation